The Naval Intelligence Geographical Handbook Series (Great-Britain, 1941-46): a description and a call for comments - Cyril Gosme (Cybergeo)
The Geographical Handbooks presented in this article were prepared and issued in Great-Britain during the Second World War under the auspices of the Intelligence Division of the Royal Navy (by Naval Intelligence Division 5) which is why the books are sometimes referred to as the ‘Admiralty Handbooks’. They offer ‘regional’ accounts on a country basis, following a systematic outline, and though they deal with only thirty or so ‘countries’ (nation-states, colonial territories, or islands), they seem to be the largest account of geographical description ever published.